Improvement of low-density lipoprotein cholesterol target achievement rates through cardiac rehabilitation for patients after ST elevation myocardial infarction or non-ST elevation myocardial infarction in Germany: Results of the PATIENT CARE registry. (29th August 2020) - Schwaab, Bernhard; Zeymer, Uwe; Jannowitz, Christina; Pittrow, David; Gitt, Anselm
Abstract: Aims: The PATIENT CARE registry aimed to document clinical characteristics of patients during cardiac rehabilitation after myocardial infarction, including the current pharmacological treatment, risk factor modification and achievement of treatment targets for low-density lipoprotein cholesterol (LDL-C). Methods: Multicentre, prospective non-interventional study at 20 cardiac rehabilitation in-patient centres across Germany. Results: A total of 1408 patients post myocardial infarction were analysed. Patients' mean age was 62 ± 11 years and 27.0% were women. ST elevation myocardial infarction ( n = 657; 48.7%), and non-ST elevation myocardial infarction ( n = 617; 45.8%) were equally balanced causes for hospitalization, while previous coronary artery bypass grafting was reported in n = 134 patients (9.9%). On average, cardiac rehabilitation began 19 ± 10 days after the index event and lasted for 22 ± 4 days. At discharge, 96.7% of patients received statins, 13.0% another lipid-lowering medication in addition to a statin, 98.5% antithrombotic drugs and 22.3% antidiabetic medication. The rate of patients with LDL-C on target according to the European Society of Cardiology/European Atherosclerosis Society dyslipidaemia guidelines 2011 (<70 mg/dl (1.8 mmol/l) or at least 50% reduction of baseline value) was increased from 21.4% at admission to cardiac rehabilitation to 41.9% at discharge after cardiac rehabilitation. Most patients (95.2%) completed the cardiac rehabilitation and 88% returned to their former work at full time. Conclusion: During cardiac rehabilitation, the modifiable cardiovascular risk factors, in particular the LDL-C, were substantially improved in patients after myocardial infarction. The great majority were able to return to work. However, less than 50% reached the LDL-C guideline targets during short-term cardiac rehabilitation.